(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Microimplants represent one of the most promising and dynamically developing areas of modern medicine, particularly dentistry and orthopedics. Their widespread introduction into clinical practice is due to unique possibilities of providing temporary anchorage support during orthodontic treatment, as well as solving complex tasks of prosthetics and reconstructive surgery.